Dekoracje irlandzkich psałterzy - Bulas, Ryszarda Maria (Vox Patrum, 2013)
A particularly interesting question in medieval Irish literature, is decorating Psalters. Since the Biblical psalms were very popular among the Anglo-Saxons, they were often copied and decorated also in Ireland. Initially, the decoration was limited to ornamentation letters. Later there were elements depicting scenes from the life of David, which had its origins, according to F. Henry, in the Carolingian art. In this article, the author presents in chronological order all decorated Irish and Anglo-Saxon Psalters, which show visible influence of the Irish art (Cathach, Durham Cassiodorus, Psalter of Cantorbury, Cotton Psalter, Southampton Psalter, Ricemarcus’ Psalter, Liber hymnorum, Psalter of the St. Caimin).